Pengaruh Literasi Asuransi, Promosi, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Asuransi Kecelakaan Diri Melalui Kepercayaan - Ahmad Fauzi; Patria Laksamana (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to examine the effect of insurance literacy, promotion, and service quality on the purchase decision of personal accident insurance products, with trust serving as a mediating variable, at PT Mitra Proteksi Madani Insurance Broker. This research employed a quantitative approach using a survey method involving the company's customers. Primary data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The findings indicate that insurance literacy, promotion, and service quality have a positive effect on trust. Promotion and service quality also have a positive and significant effect on purchase decisions, whereas insurance literacy does not have a significant direct effect on purchase decisions. Furthermore, trust does not have a significant direct effect on purchase decisions but acts as a mediating variable in the relationship between insurance literacy, promotion, service quality, and purchase decisions. These findings suggest that improving insurance literacy, implementing effective promotional strategies, and enhancing service quality, supported by stronger customer trust, can encourage consumers' purchase decisions regarding personal accident insurance products. This study is expected to contribute to the development of consumer behavior theory in the insurance industry and provide practical insights for insurance brokerage companies in developing marketing strategies and improving service quality to enhance customers' purchase decisions.